Functional electrical stimulation+iPad-based music therapy for upper limb recovery after stroke: Study protocol for a mixed methods randomised controlled trial. Issue 4 (8th August 2021) - Silveira, Tanya Marie; Dorsch, Simone; Thompson, Grace; Tamplin, Jeanette
ABSTRACT: Introduction: Music therapy offers an effective avenue for simultaneously addressing goals of upper limb function and wellbeing post stroke. However, there are currently no trials of therapeutic music-making interventions for stroke survivors with a very weak upper limb (Grade 0–3 level of strength). This randomised controlled trial will examine the effect of Functional Electrical Stimulation (FES) with iPad-based music therapy on upper limb recovery and wellbeing outcomes for stroke survivors. Method: This convergent mixed methods study will take place at seven participating hospitals in Sydney, Australia. Forty participants will be randomly allocated to usual care only or usual care plus daily FES+iPad-based music therapy for four weeks (20 sessions). Standardised assessments of the paretic upper limb and self-report wellbeing measures will be administered at three time points (pre- and post- intervention, and at three months follow up) by a blinded assessor. All participants will be interviewed about their perceptions of the way the treatment they received (usual care only or usual care plus daily FES+iPad-based music therapy) supported their recovery. Results: Ethics approval has been granted and data collection has commenced. Discussion: This treatment approach has the potential to improve upper limb function and wellbeing for stroke survivors. The intervention is novel in its capacity to engage stroke survivors with a very weak upper limb in therapeutic music-making.